2020
DOI: 10.1175/jcli-d-20-0071.1
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Coupled Chemistry–Climate Interactions in Tropical Stratospheric Temperature Variability

Abstract: The purpose of this study is to quantify the effects of coupled chemistry–climate interactions on the amplitude and structure of stratospheric temperature variability. To do so, the authors examine two simulations run on version 4 of the Whole Atmosphere Coupled Climate Model (WACCM): a “free-running” simulation that includes fully coupled chemistry–climate interactions and a “specified chemistry” version of the model forced with prescribed climatological-mean chemical composition. The results indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…1a), α eff is significantly smaller than α alone; i.e., the ozone feedback increases the radiative damping timescale compared to radiative relaxation alone. This result is consistent with the effective timescales inferred by Fueglistaler et al (2014) and with the coupled chemistry-climate model calculations in Yook et al (2020), their Fig. 6.…”
Section: Summary and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…1a), α eff is significantly smaller than α alone; i.e., the ozone feedback increases the radiative damping timescale compared to radiative relaxation alone. This result is consistent with the effective timescales inferred by Fueglistaler et al (2014) and with the coupled chemistry-climate model calculations in Yook et al (2020), their Fig. 6.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…Observations show strong correlations between ozone and temperature in the tropical lower stratosphere, and calculations show that the ozone radiative feedbacks significantly enhance temperatures, e.g., by ∼ 30 % for the annual cycle (e.g., Ming et al, 2017). This ozone feedback significantly enhances thermal variability in global model simulations (Yook et al, 2020). The goals of this work include providing an update of observational evidence for T -O 3 coupling and simplified understanding based on idealized zonal mean theory.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examine six models participating in the CCMI and five coupled chemistry-climate models participating in sixth phase of the Coupled Model Intercomparison Project (CMIP6; Eyring et al, 2016). We only include CMIP6 models with interactive stratospheric chemistry as such a coupled chemistry-climate configuration has been shown to lead to more robust interannual variability of temperatures in the lower stratosphere as compared to models with fixed ozone (Yook et al, 2020). Note that -v02.6-198401-201912-latpress-2.5deg-L31 1994-2019 3D combinedanomh2oq swoosh-v02.6-198401-201912-lonlatpress-20deg-5deg-L31 2005-2019 most of the models nevertheless simulate a too-warm cold point and too-little interannual variability of entry water (Garfinkel et al, 2021).…”
Section: Datamentioning
confidence: 99%
“…(Chae and Sherwood, 2007;Fueglistaler et al, 2011;Ming et al, 2017;Gilford and Solomon, 2017), and also by Forster et al 30 (2007) and Polvani and Solomon (2012) for decadal-scale trends. Yook et al (2020) showed that ozone feedback is an important contribution to tropical stratospheric thermal variability in global models. Birner and Charlesworth (2017) and Dacie et al (2019) have demonstrated strong sensitivity of tropical stratospheric temperatures to ozone using idealized onedimensional model calculations, following the earlier results of Thuburn and Craig (2002).…”
Section: Introductionmentioning
confidence: 99%